2015
DOI: 10.1371/journal.pone.0115332
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Disorders in Pairs of Patients and Their Family Members during and after ICU Stay

Abstract: IntroductionPatients and family members undergo different experiences of suffering from emotional disorders during ICU stay and after ICU discharge. The purpose of this study was to compare the incidence of anxiety, depression and post-traumatic stress disorder (PTSD) symptoms in pairs (patient and respective family member), during stay at an open visit ICU and at 30 and 90-days post-ICU discharge. We hypothesized that there was a positive correlation with the severity of symptoms among pairs and different pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(145 citation statements)
references
References 32 publications
8
127
1
9
Order By: Relevance
“…2,3 Looking for patient-centered outcomes, many endpoints, such as long term physical, psychological and cognitive domains, as well as patient, family, and ICU team satisfaction with therapy have all been investigated, disclosing how devastating can an ICU stay be for the critically ill 4 and their families. 5 Critically ill patients, both during their ICU stay and mainly after ICU discharge, are prone to experiencing pain, neuropathy, weakness, skin breakdowns, persistent organ function support, depression, anxiety, sleep disorders, post-traumatic stress disorder, confusion, concentration deficit, memory deficit, attention deficit, low processing speed, low visual spatial resolution ability, and low execution ability. 4,6 Within 1 to 5 years after ICU discharge, these factors ultimately result in difficult locomotion, falls, depression, poor social skills, and in up to 34% of patients a cognitive dysfunction compatible with mild Alzheimer's disease.…”
mentioning
confidence: 99%
“…2,3 Looking for patient-centered outcomes, many endpoints, such as long term physical, psychological and cognitive domains, as well as patient, family, and ICU team satisfaction with therapy have all been investigated, disclosing how devastating can an ICU stay be for the critically ill 4 and their families. 5 Critically ill patients, both during their ICU stay and mainly after ICU discharge, are prone to experiencing pain, neuropathy, weakness, skin breakdowns, persistent organ function support, depression, anxiety, sleep disorders, post-traumatic stress disorder, confusion, concentration deficit, memory deficit, attention deficit, low processing speed, low visual spatial resolution ability, and low execution ability. 4,6 Within 1 to 5 years after ICU discharge, these factors ultimately result in difficult locomotion, falls, depression, poor social skills, and in up to 34% of patients a cognitive dysfunction compatible with mild Alzheimer's disease.…”
mentioning
confidence: 99%
“…Communication about the goals of care in this setting should be a high priority as studies suggest that the effective ICU communication may diminish the psychological distress among family members of critically ill patients [10]. Many studies have shown that family members of patients who died in the ICU are at higher risk of developing PTSD [8,9,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous reports, we used a cut-off score of 30 to indicate a significant risk of PTSD [9,10]. The same person (RRLF), a psychologist with ICU interviews experience [8], conducted all interviews.…”
Section: The Instrumentsmentioning
confidence: 92%
See 2 more Smart Citations